A comparison of the regional Arctic System Reanalysis and the global ERA‐Interim Reanalysis for the Arctic1. (26th March 2015) - Bromwich, David H.; Wilson, Aaron B.; Bai, Le‐Sheng; Moore, George W. K.; Bauer, Peter
Abstract : The Arctic System Reanalysis version 1 (ASRv1), a high‐resolution regional assimilation of model output, observations and satellite data across the mid‐ and high latitudes of the Northern Hemisphere, and the global European Centre for Medium Range Forecasting Interim Reanalysis (ERAI) are compared with atmospheric observations for the period December 2006 to November 2007. Results throughout the troposphere show observations to be well assimilated in the ASRv1, as monthly and annual near‐surface (upper‐level) temperature, dew‐point (relative humidity), pressure (geopotential height) and wind‐speed biases compared with surface stations and radiosondes are very small. These results are similar to the ERAI, although wind‐speed biases are significantly smaller in the ASRv1. Despite the ASRv1's use of a 3D‐variational (Var) assimilation compared with the ERAI's 4D‐Var, similar results suggest that a regional approach with higher‐resolution terrain and a detailed land‐surface description forced by a global reanalysis may improve the assimilation of observations and help offset temporal information lost by the 3D‐Var compared with the 4D‐Var. However, the ASRv1 forecast field results compared with the ERAI are mixed. The ASRv1 and ERAI show negative precipitation biases during cool months compared with gauge observations, and too much precipitation falls in the ASRv1 during summer in the midlatitudes. Stations north of 60°N demonstrate smaller precipitation biases in the ASRv1 than the ERAI except during the summer, when the ASRv1 is very dry. Short‐wave radiation compared with observations is much too large in the ASRv1, and both reanalyses show long‐wave radiation deficits during most months. These results point to inadequacies in model physics in the ASRv1 (e.g. convective and radiation schemes) that will continue to be refined in subsequent versions of the ASR.